Nutritional, bioactive compounds content, and antioxidant activity of brown seaweeds from the Red Sea - Ismail, Mona M.; El Zokm, Gehan M.; Miranda Lopez, José M. (Frontiers in Nutrition, 2023)
Abstract Introduction: Brown seaweeds are excellent sources of bioactive molecules with a wide range of pharmacological effects, whose content can vary depending on several factors, including the origin and the environment in which the algae grow. Methods: This study aimed to estimate 19 compounds regarding primary and secondary metabolites of eight brown macroalgal species from a clean Egyptian Red Sea coast. Proximate analysis, pigment, phenolic compounds, and vitamin contents were determined. In addition, energy content and antioxidant activity were estimated to explore the potential application of algae as functional foods to encourage the species’ commercialization. Results: Based on the chemical composition, Polycladia myrica was the most valuable species, with a comparatively high protein content of 22.54%, lipid content of 5.21%, fucoxanthin content of 3.12 µg/g, β-carotene content of 0.55 mg/100 g, and carbohydrate content of 45.2%. This species also acts as a great source of vitamin C, flavonoids, tannins, phenol content and total antioxidant capacity. Discussion: The antioxidant activity of the selected algae indicated that its phenol, vitamin and pigment contents were powerful antioxidant compounds based on the structure–activity relationships. This result was verified by the strong correlation in statistical analysis at the 95% confidence level. From a worldwide perspective and based on the obtained results, these brown species may be reinforced as an essential line in future foods.